Oil Price Changes and Stock Market Performance in UAE: Evidence of Cointegration Persists in Economic Diversification era - Banerjee, Rachna; Majumdar, Sudipa; Mohammed, Zahra (International Journal of Energy Economics and Policy, 2023)
The aim of this paper is to examine the linkages between stock market index, Dubai Fateh oil spot price, interest rate and FDI using monthly data on Abu Dhabi stock index for the period 2006- 2019. Vector Autoregressive Model have been employed to analyse the relationship between the variables. Using monthly data from 2006 to 2019, the results of Vector Error Correction Model (VECM) estimates suggest that there is long-run integration between oil price and monthly stock index series in which monthly oil prices have a positive impact on stock index. The Granger Causality indicates significant bidirectional causality running from ADX index, oil price and EIBOR. Meanwhile there is unidirectional causality from stock market index to FDI. Furthermore, Impulse Response Function was employed to examine market response to oil price shocks and our study reveals that UAE stock market is efficient as it responds immediately to the oil shock. These findings are relevant for investors for portfolio management and for the policymakers such that more aggressive economic diversification policies are initiated to wane the significant persistent oil-stock integration.